(untitled) (Biological Sciences - PJSIR, 2022)
Pour colton (Gossypium hirsutumy varieties were compared for their stability of performance in 18 environments [or secdcouon yield, percentage of ginning ouuurn and staple length. Regression coefficients (b), deviations from regression (S2-d) and coefficients of variation (CY) were stability parameters considered in this investigation. Variety x environment interaction was significant which allowed further partitioning into environment linear and variety x environment linear. Environment linear and variety x environment linear were also significant, suggesting genetic differences among cultivars for their respon e to different environments. For yield and percentage of ginning outturn, variety CRTS-9 was stable indicating greater potential to perform better in a range of environments.